Extraluminal Migration Of Foreign Body In Pharynx: The End Journey Of A Stingray - A Case Report - R. Amilah; Nor Eyzawiah Binti Hassan; H. Shahrul; S. Mazlina (SCIENCEDOMAIN International, 2024)
Ingested foreign bodies are the most commonly seen emergency cases in otorhinolaryngology practice. Foreign bodies usually enter the digestive tract, and most will be passed spontaneously. Extraluminal migration of foreign bodies are relatively unusual but if it happens, it may cause serious vascular and suppurative complication. We present a 17 years old boy who swallowed a stingray fish bone. The fish bone migrated from the hypopharynx extraluminally and traversed closed to internal jugular veins. It was successfully removed by exploration of the neck and patient recovered well.